ENGLISH LEARNING MODEL: AN ETHNOGRAPHY STUDY - Maulizan Zainal Abidin; Aceng Rahmat; Zuriyati (English Education Department, 2020)
The learning model is included in the civilization process of the School. It is as a culture aiming at academic achievement, cultivates attitudes, knowledge and skills of students. The habituation learning model of the pesantren style (Islamic Boarding school) applied by MAS (Islamic Senior High School) Jeumala Amal has successfully increase the school's achievements. Based on the aforementioned data, the researcher needs to do more in-depth research in obtaining detailed information reagarding the model applied so that it is applicable for other schools. This study aims to gain a deeper understanding of the English learning model at MAS Jeumala Amal which applies a qualitative ethnographic method. The data obtained were observation, interviews, field notes and document analysis. The Study revealed that the form of English language learning is designed through a careful planning which integrates two proficiencies, namely functional and communication skills; the former are taught through classroom activities while the latter are trained more in pesantren programs. The student learning models in MAS Jeumala Amal adheres to a behavioristic pattern which emphasizes habituation in language skills through an army method pattern that restrain students based on reward and punishment pattern.